Evaluation of Antibiotics Treatment in Post Surgical RB2B Patients at H. Adam Malik Hospital - Indra Ginting; Mayang sari; Sondang Ginting (Journal La Medihealtico, 2022)
Until now, antibiotics are still the mainstay of medicine in handling infectious disease cases. Antibiotics can be defined as compounds produced by various types of microorganisms (bacteria, fungi, actinomycetes) which can suppress the growth of other microorganisms. Postoperative is the postoperative period that starts when the patient is transferred to the recovery room and ends until the next evaluation. This research was conducted in the post-surgery room of H. Adam Malik Hospital Medan. This research objective is evaluation of antibiotic treatment in post-surgical RB2B patients at H. Adam Malik Hospital Medan. This type of research is non-experimental, quantitative descriptive that conducted at RB2B of H. Adam Malik Hospital Medan from May - September 2019. The sample was all post-surgical patients in RB2B who used antibiotics, amounted to 95 patients. Based on the research conducted, there were 4 groups of antibiotics treatment in Post- Surgery RB2B. The 4 groups namely Cephalosporins, Carbapenems, Nitroimidazoles and Quinolones. The most widely used postoperative antibiotic (RB2B) was Ceftriaxone, totalling 86 vials. Then followed by infusion of Metronidazole and 44 tablets. Then in the third place, the most used is Meropenem, as many as 13 vials. Followed by the use of cefotaxime and ciprofloxacin, 6. each. And finally, the least use, namely: Cefoperazone inj as many as 5 vials. The conclusion of this study was that 60% of antibiotics prescribed in RB2B had fulfilled the Fornas, while the discrepancy according to Fornas was 40%.